A Penerangan Lampu Jalan Solar Cell dan Partisipasi Lainnya di Desa Serang Kabupaten Sumedang - Salsabila, Meivita (Jurnal Pengabdian Tri Bhakti, 2025)
The lack of street lighting in Serang Village, Sumedang Regency, especially in hamlets 1, 2, and 3, can lead to a risk of crime, especially at night. The Street Lighting Program uses Solar Cells as a solution to help the community with the problem of minimal street lighting. This program aims to provide street lighting and limited educational facilities. Other programs address core issues such as stunting, Bullying Education, and economic instability. The method used is field observation to identify problems, followed by the preparation and implementation of work programs in the fields of education, health, economy, and the environment. The results have successfully installed solar-powered street lights, implemented anti-bullying education in schools, assisted in stunting data collection, and distributed nutritious food. This program has had positive implications in the form of increased public awareness and participation, and contributed to the improvement of infrastructure, health, and education.